Effects of Body Position and Hypovolemia on the Regional Distribution of Pulmonary Perfusion During One-Lung Ventilation in Endotoxemic Pigs - Wittenstein, Jakob; Scharffenberg, Martin; Ran, Xi; Zhang, Yingying; Keller, Diana; Tauer, Sebastian; Theilen, Raphael; Chai, Yusen; Ferreira, Jorge; Müller, Sabine; Bluth, Thomas; Kiss, Thomas; et al. (Frontiers in Physiology, 2021)
Background: The incidence of hypoxemia during one-lung ventilation (OLV) is as high as 10%, and partially determined by the distribution of perfusion. During thoracic surgery, different body positions, including supine, semilateral, lateral, and prone position, are used, with the potential of influencing the distribution of perfusion. Furthermore, hypovolemia can impair hypoxic vasoconstriction. Yet, the effects of body position and hypovolemia on the distribution of perfusion remain poorly defined. We hypothesized that, during OLV, the relative perfusion of the ventilated lung is higher in the lateral decubitus than other positions, and that hypovolemia impairs the redistribution of pulmonary blood flow. Methods: Sixteen juvenile pigs were anesthetized, mechanically ventilated, submitted to a right-sided thoracotomy, and randomly assigned to one of two groups: 1) intravascular normovolemia, or 2) intravascular hypovolemia, as achieved by draw of approximately 25% of the estimated blood volume (n=8/group). To mimic thoracic surgery inflammatory conditions, Escherichia coli lipopolysaccharide was continuously infused at 0.5 µg kg-1 h-1. Under left-sided OLV, animals were further randomized to one of four sequences of supine, left semilateral, left lateral and prone positioning. Measurements of pulmonary perfusion distribution with fluorescence-marked microspheres, ventilation distribution by electro-impedance tomography, and gas exchange were performed during two-lung ventilation in supine position and after 30 min in each position and intravascular volume status during OLV. Results: During OLV, the relative perfusion of the ventilated lung was higher in lateral than supine position. Relative perfusion of the non-ventilated lung was lower in lateral than supine and prone position, and in semilateral compared to prone position. During OLV, highest PaO2/FIO2 (arterial partial pressure of oxygen/ inspiratory fraction of oxygen) was achieved in lateral as compared to all other positions. The distribution of perfusion and ventilation, as well as oxygenation, did not differ significantly between normo- and hypovolemia. Conclusions: During OLV in pigs, the relative perfusion of the ventilated lung and oxygenation were higher in lateral than supine position, and not impaired by hypovolemia.